Detection-criterion independent proof for digital watermark detection : a support vector machine approach - Then,, Patrick Hang Hui (Faculty of Computer Science and Information Technology, 2007)
Perceiving digital watermark detection as image classification problem stands as the basic of the detector criterion independent zero-knowledge watermark detection proof using Support Vector Machine (SVM). In-depth insights are given to using SVM to enable detection criterion independent zero-knowledge watermark detection protocol. The existing zero-knowledge watermark detection protocols are analysed and re-designed to be detection criterion independent zero-knowledge watermark detection protocol.